Odprti podatki kot pospeševalec družbenih, okoljskih in gospodarskih inovacij – priložnosti in izzivi (University of Maribor Press, 2026)
Open Data as a Driver of Social, Environmental, and Economic Innovation – Opportunities and Challenge. The scientific monograph Open Data as a Driver of Social, Environmental, and Economic Innovation – Opportunities and Challenges provide a comprehensive and interdisciplinary insight into the development, governance, and use of open data and their impacts on the data economy. Across eight thematically complementary chapters, the authors examine the legal and governance frameworks of open data, international and national trends, data quality issues, and the role of open data in fostering innovation. Emphasis is placed on the development of methodologies for the qualitative evaluation of open data and for measuring enterprises’ maturity to use open data. The monograph integrates theoretical foundations, empirical analyses, and practical tools, offering valuable guidance for researchers, policymakers, data managers, and enterprises seeking to better understand and more effectively harness the potential of open data for sustainable and innovation-driven societal development.